PH-responsive thiolated chitosan nanoparticles for oral low-molecular weight heparin delivery: in vitro and in vivo evaluation. (2nd January 2016) - Fan, Bo; Xing, Yang; Zheng, Ying; Sun, Chuan; Liang, Guixian
Abstract: The aim of present study was to investigate a pH-responsive and mucoadhesive nanoparticle system for oral bioavailability enhancement of low-molecular weight heparin (LMWH). The thioglycolic acid (TGA) was first covalently attached to chitosan (CS) with 396.97 ± 54.54 μmol thiol groups per gram of polymer and then the nanoparticles were prepared with thiolated chitosan (TCS) and pH-sensitive polymer hydroxypropyl methylcellulose phthalate (HPMCP) by ionic cross-linking method. The obtained nanoparticles were characterized for the shape, particle size, zeta potential, drug entrapment efficiency and loading capacity. In vitro results revealed the acid stability of pH-responsive nanoparticles, which had a significant control over LMWH release and could effectively protect entrapped drugs in simulated gastric conditions. By the attachment of the thiol ligand, an improvement of permeation-enhancing effect on freshly excised carp intestine (1.86-fold improvement) could be found. The mucoadhesive properties were evaluated using fluorescently labeled TCS or CS nanoparticles. As compared with the controls, a significant improvement of mucoadhesion on rat intestinal mucosa was observed in TCS/HPMCP nanoparticles via confocal laser scanning microscopy. The activated partial thromboplastin time (APTT) was significantly prolonged and an increase in the oral bioavailability of LMWH was turned out to be pronounced after oral delivered LMWH-loaded TCS/HPMCP nanoparticles in rats, which suggested enhanced anticoagulant effects and improved absorption of LMWH. In conclusion, pH-responsive TCS/HPMCP nanoparticles hold promise for oral delivery of LMWH.